Investigation of the characteristics differentiating complicated and non-complicated appendicitis: A prospective analysis (Annals of Medical Research, 2021)
Aim: To investigate preoperative laboratory and clinical results and imaging methods in patients with complicated and non-complicated appendicitis.Materials and Methods: A total of 141 patients aged over 16 years, who underwent surgery with the diagnosis of acute appendicitis, were included in the study. In patients diagnosed with acute appendicitis based on physical examination and laboratory findings, abdominal contrast-enhanced tomography was performed for confirmation and differential diagnosis. Age, gender, body temperature, complaint, duration of complaint, number of white blood cells, the largest diameter of appendicitis measured on computed tomography (CT), Alvarado score, and recurrent admission to any health institution with the same complaint were recorded. Intraoperative findings and pathology reports were evaluated to determine whether the appendicitis was complicated, and the cases were divided into two groups as complicated and non-complicated. Results: Totally 141 patients were included in the study, 39 cases were classified as complicated and 102 cases as non-complicated appendicitis. There were more people with high fever in the complicated group (p=0.023). The median of largest appendicitis diameter measured on the CT was 8.5 (5.5-15) mm, and a significant difference was determined between the two groups in terms of diameter (p0.001). The median time from the onset of the complaints to the emergency department presentation was 12 hours, and this duration was significantly longer in the complicated group (p0.001). Analysis of receiver operating characteristic curves yielded the cutoff values of 8.35 mm for diameter (area under the curve [AUC]: 0.860; sensitivity: 87.2%; specificity: 63.7%), and 10.5 hours for time interval (AUC: 0.868; sensitivity: 97.4%; specificity: 64.7%) were found to be the best predictive values for the complicated acute appendicitis determination.Conclusion: In patients diagnosed with acute appendicitis, necessary interventions should be immediately undertaken, especially in the presence of fever, increased appendicitis diameter, and delayed presentation to hospital.